THE ACQUISITION OF SPATIAL COMPETENCE – FAST AND EASY MULTIDISCIPLINARY LEARNING WITH AN ONLINE GIS - Friedrich BARNIKEL; Robert PLOETZ (European Journal of Geography)
The acquisition of spatial competence can be considered one of the major tasks of the subject Geography at our secondary schools. In this context teachers are sincerely asked to not only complain about the ubiquity of modern digital media (e.g. when students receive messages in their classrooms during teaching…) but to make use of it! The wide scientific field of maps and mapping competence offers fantastic opportunities to easily create and manipulate digital maps and, by doing that, helps the students reach a deeper understanding of how to illustrate space and content in an attractive way and how to navigate uncharted waters. This paper shows some small and easy best-practice examples of fast and simple multidisciplinary approaches with online GI services from a German high school to be used at secondary schools all over Europe.